BIONOMICS AND EVALUATION OF DIFFERENT BIO PESTICIDES AGAINST HELICOVERPA ARMIGERA (HUBNER) HARDWICK INFESTING GROUNDNUT - H. A. GADHIYA; P. K. BORAD; J. B. BHUT (The Bioscan, 2013)
Studies on bionomics of Helicoverpa armigera (Hubner) Hardwick on groundnut under laboratory conditions revealed that freshly laid eggs were nearly hemispherical round shaped with flattened base, giving a shining yellowish white at first and changing to dark brown prior to hatching. The incubation period of egg was 2 to 4 days. There were five larval instars length of completely developed larva was 26 to 30 mm and larval period was 3 to 7 days. The pre-pupal period was 1 to 4 days. The pupal period was different for both male and female, it was 15 to 18 and 14 to 20 days, respectively. The sex of adult moths were differentiated in the pupal stage by examining the location of genital slit in relation to anal slit. The total life span for male and female was 49.40 ± 5.21 and 52.40 ± 7.03 days, respectively. The fecundity was 255.88 ± 43.21 eggs per female. The sex ratio (male : female) was 1 : 1.12 and 1 : 1.13 under laboratory and field condition, respectively. Out of the nine bio pesticides evaluated against H. armigera infesting groundnut, HaNPV (450 LE/ha) was noticed most effective against H. armigera and also registered highest yield among all treatments.